2021
DOI: 10.1007/s00431-021-04101-3
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation heterogeneity in children with severe asthma

Abstract: Small airway disease, characterised by ventilation heterogeneity (VH), is present in a subgroup of patients with asthma. Ventilation heterogeneity can be measured using multiple breath washout testing. Few studies have been reported in children. We studied the relationship between VH, asthma severity, and spirometry in a cross-sectional observational cohort study involving children with stable mild-moderate and severe asthma by GINA classification and a group of healthy controls. Thirty-seven participants aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The mean values of spirometric parameters (FEV1, FEV/FVC, FEF25-75) were within the normal range, and only in about one-third of the cases FEV1 values were below 80% of predicted. This result, which might be partly due to long term treatment with biologics in some of the children, is consistent with previous studies showing that spirometry is often normal in pediatric severe asthma, while other tests, such as lung clearance index, can show an earlier deterioration (15).…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 92%
“…The mean values of spirometric parameters (FEV1, FEV/FVC, FEF25-75) were within the normal range, and only in about one-third of the cases FEV1 values were below 80% of predicted. This result, which might be partly due to long term treatment with biologics in some of the children, is consistent with previous studies showing that spirometry is often normal in pediatric severe asthma, while other tests, such as lung clearance index, can show an earlier deterioration (15).…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 92%
“…While the magnitude of LCI and S cond changes observed is small and their clinical importance remains to be determined, it is possible that even small changes could have functional relevance. For instance, we and others have also shown that LCI is elevated, although mildly only, in many severe asthmatics as compared with those without severe asthma 43,44 . Several studies have also examined the utility of MBW in preschool asthma, and some 45,46 but not all 47 studies reported higher LCI values with an asthma diagnosis, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, we and others have also shown that LCI is elevated, although mildly only, in many severe asthmatics as compared with those without severe asthma. 43,44 Several studies have also examined the utility of MBW in preschool asthma, and some 45,46 but not all 47 studies reported higher LCI values with an asthma diagnosis, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…• Даже при нормальном значении ОФВ1 у каждого пятого пациента с тяжелой БА снижается индекс легочного клиренса, что свидетельствует о дисфункции малых дыхательных путей, т. е. неоднородной вентиляции периферических отделов [25][26][27].…”
Section: морфофункциональные особенности и вентиляция легких у пациен...unclassified